Examining the relationship between procurement strategies and organizational performance of Ghanaian firms: How does strategic procurement drive organizational success? - Godfrey Adda (Economics, Management and Sustainability)
This study investigates the impact of procurement strategies – Strategic Procurement (STRP), Supplier Relationship Management (SRM), Risk Management Practices (RMP), and Sustainable Procurement (SUSP) – on organizational performance among industrial firms in Ghana’s Greater Accra region. A structured questionnaire was administered to 500 participants from industrial companies, resulting in 437 valid responses (an 87.4% response rate). Data were analyzed using partial least squares structural equation modeling (SEM-PLS). We used non-probability and purposive sampling methods to select firms from a list provided by the Association of Ghana Industries. The results show that Strategic Procurement significantly enhances organizational performance. SRM positively influences Strategic Procurement but does not directly impact performance. RMP positively affects both strategic procurement and organizational performance, whereas sustainable procurement positively influences both. The mediation analysis reveals that Strategic Procurement partially mediates the effects of Sustainable Procurement and RMP on organizational performance. However, Strategic Procurement does not mediate the relationship between SRM and organizational performance, suggesting that other mechanisms may drive this relationship. This study highlights the central role of Strategic Procurement in linking sustainable procurement and RMP to improve performance. This emphasizes the need for a holistic approach to procurement strategy, integrating sustainable and risk management practices for optimal outcomes in Ghana’s industrial sector. Organizations should align procurement strategies with strategic goals, foster strong supplier relationships, embed risk management in procurement processes, and integrate sustainability for regulatory compliance and reputational benefits. In addition, organizations should implement performance metrics for continuous improvement.